Analisis Reaksi Pasar dan Pergantian Auditor Sebelum dan Sesudah Restatement - Firma Agista; Sudrajat Sudrajat; Yenni Agustina (Jurnal Ilmiah ESAI, 2023)
The purpose of this study is to analyze whether there are differences in market reactions and auditor changes before and after the restatement the company. In this study, three variables were used, market reaction, auditor changes and restatement. This research used quantitative method.  The populations are all company listed on Indonesia Exchange IDX in the period of 2017 to 2019 taken with purposive sampling method. The test method uses the Wilcoxon Signed Rank-Test test because the normality test shows that the data are not normal. The data were processed using IBM SPSS Statistics 26.  The results show that there is a difference in the average abnormal return before and after the restatement; there is no difference in the average trading volume activity before and after the restatement; and there is no difference in the change of auditors before and after the restatement because the change of auditors has been regulated in Indonesian regulations.